臺灣國民核心素養與中小學課程發展之關係The Relation between the Core Competences and Elementary and Secondary School Curriculum Development in Taiwan - 陳伯璋Po-Chang Chen (Journal of Curriculum Studies, 2010)
本研究旨在針對18歲以下國民，進行全方位的國民核心素養之研究，並建構與臺灣中小學課程發展之關係。根據理論探究，乃歸納三維立論依據，分別是「全球化與在地化」、「學校內與學校外的環境變遷」、「過去、現在與未來社會」等面向探討臺灣國民核心能力素養之關鍵指標。透過課程綱要的課程目標，界定其架構與內涵，以供教育人員據此進行課程規劃、設計、實施與評量，並且確定學習者的達成程度；特別是國民教育核心素養的課程目標，必須與學習領域的課程內容、教學運作與實施通則、學習評量等進行緊密連結。此外，本研究亦分析國家教育研究院K-12中小學課程發展之基礎研究，提出此一浩大工程的研究，以國家教育核心素養為重心的課程發展機制永遠發展的可能性和必要性。The study researched into the full spectrum of the core competences of Taiwan nationals under age of 18 and established the relation between the core competences and elementary and secondary school curriculum development. By theory inquiry, the study explored the key indicators of the core competences from three dimensions, “globalization and localization,” “environment change within and outside the schools,” and “past, present, and future society.” Based on the goals of the curriculum guideline, the study defined the structure and content of the core competences for educators. Thus, they can to do curriculum planning and design evaluation to make sure the learning effect. The curriculum goals of the core competences especially, must link closely with course content, general principle of teaching practice, and leaning evaluation of the learning area. Besides, an analysis about the foundamentary researches on K-12 curriculum development undertaken the National Academy of Educational Research which are based on key competences are suggested as necessary mechanism in curriculum development of Taiwan.